Hubungan Pola Makan Terhadap Kejadian Gastritis Pada Mahasiswa Fakultas Kesehatan Universitas Muhammadiyah Sukabumi - Febbi Adha Hardiani; Amir Hamzah; Egi Mulyadi (NAJ Nursing Applied Journal, 2025)
Eating patterns are a person's way or effort in organizing and choosing and using food ingredients every day, including types of food, frequency of eating and portions of food by paying attention to health factors and nutritional status. Students are often trapped in unhealthy and irregular lifestyles, even experiencing eating disorders. Eating disorders can cause gastritis symptoms ranging from mild to severe. This study aims to determine the relationship between diet and the incidence of gastritis in health faculty students at Muhammadiyah University, Sukabumi. This research method uses a quantitative method with descriptive correlation using a cross sectional approach on 83 health faculty students using purposive sampling techniques. statistical analysis using the chi-square test. The results of this study were 43 out of 83 people (51.8%) with poor eating patterns with a P value of 0.000 < 0.005. The conclusion is that there is a relationship between diet and the incidence of gastritis in health faculty students at Muhammadiyah University, Sukabumi.